1996
DOI: 10.1074/jbc.271.15.8895
|View full text |Cite
|
Sign up to set email alerts
|

Variant AE2 Anion Exchanger Transcripts Accumulate in Multiple Cell Types in the Chicken Gastric Epithelium

Abstract: Molecular analyses have resulted in the isolation of two chicken stomach AE2 anion exchanger cDNAs, AE2-1 and AE2-2. The ϳ4.3-kilobase (kb) AE2-1 cDNA contains an open reading frame that encodes a predicted polypeptide of ϳ135 kDa that is homologous to AE2 anion exchangers from other species. The partial ϳ1.7-kb AE2-2 cDNA, which differs from the AE2-1 cDNA in two regions, would be predicted to encode an AE2 polypeptide with an alternative N-terminal cytoplasmic tail. Examination of the distribution of these v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…AE1 (previously termed band 3) is a founding member of the sodium-independent Cl Ϫ /HCO 3 Ϫ -exchanger gene family, which according to the current knowledge consists of at least two additional members, namely AE2 and AE3 [13][14][15][16][17][18]. In addition, each gene produces tissue-specific variants by means of alternative splicing and/or by the use of alternative promoters [19][20][21][22]. AE1 is found in erythrocytes, kidney, and heart [18,19,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AE1 (previously termed band 3) is a founding member of the sodium-independent Cl Ϫ /HCO 3 Ϫ -exchanger gene family, which according to the current knowledge consists of at least two additional members, namely AE2 and AE3 [13][14][15][16][17][18]. In addition, each gene produces tissue-specific variants by means of alternative splicing and/or by the use of alternative promoters [19][20][21][22]. AE1 is found in erythrocytes, kidney, and heart [18,19,23].…”
Section: Introductionmentioning
confidence: 99%
“…AE1 is found in erythrocytes, kidney, and heart [18,19,23]. AE2 is found in almost all tissues, but mainly in the stomach, kidney, and intestine [21,24,25]. AE3 is expressed predominantly in the brain and heart [17,26].…”
Section: Introductionmentioning
confidence: 99%
“…4). Secondly, tissue sections from the stomach, which expresses the AE2 anion exchanger at high levels (Cox et al 1996), were also negative for staining with the AE1 antiserum (Fig. 5).…”
Section: Resultsmentioning
confidence: 98%
“…12B). The fact that the sequence between amino acids 185-203 of AE1-1b is not conserved in the AE2 (Cox et al 1996) and AE3 (Kudrycki et al 1990) anion exchangers strongly suggests that the multiple species observed in the CAM are all derived from the AE1 gene. Whether the multiple species observed in the CAM are the result of differential glycosylation of a single AE1 variant or are derived from multiple variant AE1 transcripts awaits further analysis.…”
Section: Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation